2012
DOI: 10.1097/yct.0b013e318250058c
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Transcranial Magnetic Stimulation in Depressed Adolescents

Abstract: Transcranial magnetic stimulation is relatively well tolerated by depressed adolescents, but it is also perceived as mostly unhelpful by them and their parents. This is at odds with emerging studies suggesting that rTMS can be an effective and safe treatment in this age group, indicating that further research is required to confirm our findings and understand reasons for any disparity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…(A treatment in which a magnetic field is used),” and most reported that they would agree to be treated with rTMS if recommended in the future. 20 , 21 …”
mentioning
confidence: 99%
“…(A treatment in which a magnetic field is used),” and most reported that they would agree to be treated with rTMS if recommended in the future. 20 , 21 …”
mentioning
confidence: 99%
“…However, it is not clear to what extent this was influenced by the monetary compensation provided. In other tDCS studies too (stroke rehabilitation) participants also reported feelings of discomfort (Tedesco Triccas et al, 2018 ), whereas individuals receiving rTMS for depression did not raise such concerns (Walter et al, 2001 ; Mayer et al, 2012 ). RTMS was perceived as less frightening than “having something done at the dentist” by most adults (88%) (Walter et al, 2001 ) and less than half of adolescents (37.5%) (Mayer et al, 2012 ).…”
Section: Discussionmentioning
confidence: 98%
“…In other tDCS studies too (stroke rehabilitation) participants also reported feelings of discomfort (Tedesco Triccas et al, 2018 ), whereas individuals receiving rTMS for depression did not raise such concerns (Walter et al, 2001 ; Mayer et al, 2012 ). RTMS was perceived as less frightening than “having something done at the dentist” by most adults (88%) (Walter et al, 2001 ) and less than half of adolescents (37.5%) (Mayer et al, 2012 ). This difference could be due to the fact that 2/3 of the adult sample in that study had previously had ECT (Walter et al, 2001 ), whereas the adolescents would have been more treatment naïve.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Early evidence also suggests that treatment of resistant depression by rTMS in adolescents is not associated with long-term cognitive deterioration and that some patients may derive long-term benefit from rTMS 23. However, although rTMS is relatively well tolerated in adolescent patients with major depression, there are also reports suggesting that rTMS may not be perceived as being very helpful by patients and their parents,24 and its efficacy in adolescents has only been evaluated in a small number of open-label studies.…”
Section: Introductionmentioning
confidence: 99%